Students with Speech Impairments Participating in Recess - Lucas, Matthew D.; Watson, Carolyn R. (Journal of the American Academy of Special Education Professionals, 2013)
The participation of students with speech impairments in recess can often be both challenging and rewarding for the students and teachers. This paper will address common characteristics of students with speech impairments and present basic solutions to improve the experience of these students in the recess setting. Initially the definition, symptoms, and prevalence of speech impairments will be presented. The paper will then address the special education classification of children with speech impairments, benefits of recess for children with speech impairments, and recommendations for these children in recess.